Isolation and estimation of flavonoid compound(s) of Baccharoides anthelmintica (L.) Moench. Issue 8 (18th April 2022) - Kumar, Deepak; Kaur, Amanpreet; Madaan, Reecha; Kumar, Suresh
Abstract: Based on ethnobotanical surveys, an Indian traditional plant, i.e., Baccharoides anthelmintica (L.) Moench (Family – Asteraceae) was selected for detailed phytochemical investigations. B. anthelmintica seeds, purchased from local market, were extracted exhaustively in a Soxhlet apparatus using methanol as solvent. A well-established method was adopted to obtain phenolic compounds and flavonoids rich fraction of methanol extract. This fraction yielded two isolates (AK-1 and AK-2) upon purification by column chromatographic process. AK-1 was characterized as mixture of two isomeric compounds − 3′, 4′, 5, 6, 7- and 3′, 4′, 5, 7, 8-pentahydroxy flavanone, and AK-2 as butein (chalcone derivative) by UV, IR and NMR spectral analysis. A TLC densitometric method was developed and validated to estimate the content of butein in B. anthelmintica seeds, and was found to be 1.252 mg/g. Bioactive Marker (butein) based standardized B. anthelmintica seeds will ensure reproducibility in efficacy and safety of the plant or authenticity of its products. Graphical Abstract: